EFEKTIVITAS PENDIDIKAN ANAK DI LINGKUNGAN KELUARGA DALAM PEMBENTUKAN MORAL ANAK USIA DINI - Hardiyana, Andri; Afiani, Wilda Fadlilati; Fajria, Nesa Ramatun (NANAEKE: Indonesian Journal of Early Childhood Education, 2022)
Education is important. The first and foremost education is the education provided by the family because the family is the closest environment for children and it is in the family environment that children spend more time than in the school environment. Education given to children is not only about mastery and knowledge but also includes moral education. Moral formation in early childhood begins in the immediate environment, namely the family environment. The family environment is a very important environment, so the purpose of this research is to find out how the effectiveness of children's education in the family environment in the formation of early childhood morals about how parents shape morals in children. This study uses qualitative methods, data collection techniques carried out through observation and interviews, it can be concluded that the family environment has a major influence on the moral values ​​of children. A good family environment will produce good children and vice versa a poor environment results. It will not be good. In addition, moral formation in early childhood is the beginning for further development